Effectiveness of an Education Program on Nurses Knowledge toward Care of Chest Tube in Children at Pediatric Teaching Hospital Baghdad City - Hassan Ali Jabar; Afifa Radha Aziz (Indian Journal of Forensic Medicine & Toxicology, 2021)
Study background: A chest tube is a drain that is inserted into the pleural cavity space to extract air, fluid, or blood to restore negative pressure to the pleural space, re-expand a partially collapsed lungs, and prevent reflux or leakage back into the chest. Since the pleural cavity’s .Methodology :The study was designed as quiz-experiment design using test retest approach for study groups .The sample (30) nurses enrolled as a control group and (30) nurses enrolled as a study group participants were exposed to an educational program pre test1, post test1 post test 2 .Results: The results of the study indicate that there are differences with the high test between the previous and post-test in the experimental group (the study group) in the main general axes with nursing knowledge care chest Table (4-2-2) shows summary statistics concerning nurses’ knowledge of the chest tube related to formed questionnaire’s items along (Pre, Post1, and Post2) studied periods due to applying a proposed of an educational program for the study group the table shows the assessments Intervals scoring scales of relative Sufficiency Coefficient (RS%): [L: Low (0.00 – 33.33)]; [M: Moderate (33.34 – 66.66)]; [H: High (66.67 – 100)]. The results of controlled group has recorded marginal immovable responses over the three periods of times with low levels or moderate but all of studied items illustrated too highly and meaningful changeability with highly levels of evaluations along (pre-post2) periods.Conclusion: There is a significant relationship between the pre-test and post test result of educational program also significant nurses’ response concerning nursing knowledge chest tube care.Recommendations: The nurses’ are provided with suitable training to participate in the program and receive information on the best way to encourage communities they serve to get chest tube care in children